การศึกษาผลการพัฒนาความคิดและผลงานสร้างสรรค์จากกิจกรรมศิลปะกระดาษสร้างสรรค์ของผู้เรียนระหว่าง 10-12 ปี โดยใช้แนวคิดสังคมอุดมฮัก (GCK4S) The Effect of Creative Art Activities from Papers of 10-12 years Learners by using the Hug Social (GCK4S) Approach. - เต็งเจริญกุล ชลธาร (Journal of Fine and Applied Arts Khon Kaen University, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์ของการวิจัย คือ 1) เพื่อศึกษาความคิดสร้างสรรค์ ของผู้เรียนอายุระหว่าง 10-12 ปีจากกิจกรรมศิลปะกระดาษสร้างสรรค์โดยใช้รูปแบบสังคมอุดมฮัก (GCK4S) มีจำนวนผู้เรียนผ่านตามเกณฑ์ร้อยละ 70 ขึ้นไป 2) เพื่อศึกษาผลงานสร้างสรรค์ ของผู้เรียนอายุระหว่าง 10-12 ปี จากกิจกรรมศิลปะกระดาษสร้างสรรค์โดยใช้รูปแบบสังคมอุดมฮัก (GCK4S) มีจำนวนผู้เรียนผ่านตามเกณฑ์ร้อยละ 70 ขึ้นไป และ 3) เพื่อศึกษาความพึงพอใจของผู้เรียนอายุระหว่าง 10-12 ปี จากกิจกรรมศิลปะกระดาษสร้างสรรค์โดยใช้รูปแบบสังคมอุดมฮัก (GCK4S) การวิจัยครั้งนี้ ใช้กลุ่มเป้าหมาย ได้แก่ ผู้เรียนอายุระหว่าง 10-12 ปี โรงเรียนฮักสคูล จังหวัดขอนแก่น จำนวน 6 คน เป็นการวิจัยเชิงทดลองเบื้องต้น (Pre-Experimental Design) โดยศึกษาแบบ One-Shot Case Study เครื่องมือที่ใช้ในการวิจัยประกอบด้วย 1) แผนการจัดการเรียนรู้ โดยใช้กิจกรรมศิลปะกระดาษสร้างสรรค์ ของผู้เรียนอายุระหว่าง 10-12 ปี โดยใช้แนวคิดสังคมอุดมฮัก (GCK4S) วิชา ศิลปะสำหรับวัยรุ่น (Art for Teen) เรื่องทัศนธาตุ จำนวน 8 แผน 16 ชั่วโมง 2) แบบทดสอบวัดความคิดสร้างสรรค์จากผลการวาดภาพ (TCT-DP) โดย Urban & Jellen จำนวน 1 ชุด 3) แบบสอบถามความพึงพอใจที่มีต่อการจัดการเรียนรู้ กิจกรรมศิลปะกระดาษสร้างสรรค์ ของผู้เรียนอายุระหว่าง 10-12 ปี โดยใช้แนวคิดสังคมอุดมฮัก (GCK4S) จำนวน 1 ชุด 4) แบบสังเกตพฤติกรรมการเรียนรู้ จำนวน 1 ชุด และ 5) แบบประเมินผลงานการเรียนรู้ สถิติที่ใช้ในการวิเคราะห์ข้อมูล คือ ค่าเฉลี่ย () ส่วนเบี่ยงเบนมาตรฐาน (S.D.) และค่าร้อยละ ผลการวิจัยพบว่า 1) ความคิดสร้างสรรค์ ของผู้เรียนอายุระหว่าง 10-12 ปี จากกิจกรรมศิลปะกระดาษสร้างสรรค์โดยใช้รูปแบบสังคมอุดมฮัก (GCK4S) มีคะแนนเฉลี่ยรวม 59.66 คิดเป็นร้อยละ 82.86 มีจำนวนมีผู้เรียนผ่านเกณฑ์ จำนวน 6 คน คิดเป็นร้อยละ 100 2) ผลงานสร้างสรรค์ ของผู้เรียนอายุระหว่าง 10-12 ปี จากกิจกรรมศิลปะกระดาษสร้างสรรค์โดยใช้รูปแบบสังคมอุดมฮัก (GCK4S) มีคะแนนเฉลี่ย 381.16 คิดเป็นร้อยละ 82.15 มีจำนวนผู้เรียนผ่านเกณฑ์จำนวน 6 คน คิดเป็นร้อยละ 100 และ3) ผลการศึกษาความพึงพอใจของผู้เรียนอายุระหว่าง 10-12 ปี จากกิจกรรมศิลปะกระดาษสร้างสรรค์โดยใช้รูปแบบสังคมอุดมฮัก (GCK4S) พบว่าผู้เรียนมีความพึงพอใจในระดับ พอใจมากที่สุด โดยมีคะแนนเฉลี่ย 4.78 The objectives of this research are 1) to examine the creativity of the learners aged between 10-12 years old, 70 percent of whom were qualified, through the creative paper art activities using the hug social (GCK4S) approach, 2) to assess the creative pieces of work of the learners aged between 10-12 years old, 70 percent of whom were qualified, through the creative paper art activities using the hug social (GCK4S) approach, and 3) to investigate the satisfaction of the learners aged between 10-12 years old through the creative paper art activities using the hug social (GCK4S) approach. The participants of this research were six learners aged between 10-12 years old at Hug School in Khon Kaen Province. This research is a pre-experimental designed research that was conducted with one-shot case study. The instruments used were 1) eight lesson plans of Art for Teen for the total of 16 hours on the topic of visual elements, utilizing the creative paper art activities using the hug social (GCK4S) approach, 2) one set of the Test for Creative Thinking-Drawing Production (TCT-DP) by Urban & Jallen, 3) one set of satisfaction questionnaires for assessing the satisfaction toward the conduction of the creative paper art activities using the hug social (GCK4S) approach for 10-12 year-old learners, 4) one set of learning behavior observation form, and 5) Holistic Rubrics summative evaluation form. The obtained data was analyzed to carry out mean (), standard deviation (S.D.), and percentage. The results were as follows. 1) According to the creativity examination of the learners aged between 10-12 years old through the creative paper art activities using the hug social (GCK4S) approach, it was revealed that six students, 100 percent, were qualified. Their mean score was 59.66 or 82.86 percent, which were above the requirement. 2) The assessment of the creative pieces of work of the learners aged between 10-12 years old through the creative paper art activities using the hug social (GCK4S) approach disclosed that all six students, 100 percent, scored 381.16 on average, which was 82.15 percent and met the requirement. 3) Regarding the investigation of the satisfaction of the learners aged between 10-12 years old through the creative paper art activities using the hug social (GCK4S) approach, it was obvious that the learners were most satisfied with the mean of 4.78.